2013
DOI: 10.1021/ac302943q
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Impedance Detection of Cancer Cells

Abstract: Ovarian cancer cells, SKOV3, have been immobilized onto platinum microelectrodes using anti-EPCAM capture antibodies and detected with high sensitivity using electrochemical impedance. The change in impedance following cell capture is strongly dependent on the supporting electrolyte concentration. By controlling the concentration of Dulbecco's phosphate buffered saline (DPBS) electrolyte, the double layer thickness can be manipulated so that the interfacial electric field interacts with the bound cells, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…Cell capture further decreases (by 42%) the capacitance to 40 73 m F cm À 2 , which is again consistent with impeded ion and solvent to the surface of the underlying electrode. Significantly, consistent with previous reports (Bard and Faulkner, 2001;Bourdillon et al, 1993;Kim et al, 2012;Venkatanarayanan et al, 2013), ESI -Figs. S4 and S5, the peak-to-peak separation for the oxidation of the ferrocene methanol does not change significantly following antibody immobilization suggesting that at the slow scan rate used, the rate of heterogeneous electron transfer to the ferrocene does not influence the voltammetric response.…”
Section: Electrochemical Characterizationsupporting
confidence: 93%
See 2 more Smart Citations
“…Cell capture further decreases (by 42%) the capacitance to 40 73 m F cm À 2 , which is again consistent with impeded ion and solvent to the surface of the underlying electrode. Significantly, consistent with previous reports (Bard and Faulkner, 2001;Bourdillon et al, 1993;Kim et al, 2012;Venkatanarayanan et al, 2013), ESI -Figs. S4 and S5, the peak-to-peak separation for the oxidation of the ferrocene methanol does not change significantly following antibody immobilization suggesting that at the slow scan rate used, the rate of heterogeneous electron transfer to the ferrocene does not influence the voltammetric response.…”
Section: Electrochemical Characterizationsupporting
confidence: 93%
“…3A is that, following deposition of the antibody layer, the formal potential of ferrocene increases by approximately 57 mV, indicating that it is harder to oxidize ferrocene in the presence of the antibody layer and even more after cell capture. We have shown previously (Venkatanarayanan et al, 2013) that when the electrolyte concentration was high (0.1 M) the shape of the Nyquist response did not depend strongly on the antibody and cell concentration. However, in dilute electrolytes (0.001 M) the electrical double layer extends further out into solution and both the cell resistance and the capacitance depend on the antibody and cell concentration (surface coverage) -ESI -Figs.…”
Section: Electrochemical Characterizationmentioning
confidence: 84%
See 1 more Smart Citation
“…The design and development of rapid, noninvasive, highly sensitive, and specific techniques for evaluating SA expression level are therefore important. In recent years, electrochemical impedance spectroscopy (EIS) has become a popular approach in a broad range of fields, including semiconductor batteries, corrosion, fuel cells, and biosensors (Chang and Park, 2010;Sherif and Park, 2006;Venkatanarayanan et al, 2013;Wang et al, 2014c). In particular, EIS has been widely applied in living cell measurements; for example, Zhu et al reported a highly sensitive impedance sensor for HL-60 cells, based on carboxylic single-walled carbon nanotube/Au composites (Zhang et al, 2009), Ju et al used electrochemical impedance detection of K562 leukemia cells (Ding et al, 2007), and Wang et al prepared folate conjugated-polyethylenimine carbon nanotubes for HeLa cell detection using EIS .…”
Section: Introductionmentioning
confidence: 99%
“…Fatoyinbo et al [5] have measured biophysical parameters of cells (cytoplasmic conductivity, membrane conductivity and cell wall conductivity) by analysing its cells DEP behaviour. Moreover, IA was also advantageous to detect ovarian cancer cells SKV3 [6] or to detect insulin levels in blood serum [7] so as to predict diabetes or trauma. Here we present a specific, miniaturized and compact equipment solution to a fully automated and controlled bacteria concentration device.…”
Section: Introductionmentioning
confidence: 99%